2023
DOI: 10.1212/wnl.0000000000207261
|View full text |Cite
|
Sign up to set email alerts
|

Head Trauma in Refugees and Asylum Seekers

Abstract: Background and Objectives:Refugees and asylum-seekers are at risk for head trauma. They endure blows to the head due to exigent circumstances necessitating resettlement (e.g., torture, war, interpersonal violence), as well as during their dangerous journeys to refuge. Our objective was to assess the global prevalence of head trauma in refugees and asylum-seekers and describe its clinical characteristics in this population.Methods:The protocol was registered in the PROSPERO International Prospective Register of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…14 Gang violence and interpersonal violence is also associated with a higher prevalence of TBI, which is reported in as many as 78% of refugees and asylum seekers, although prevalence estimates are wide-ranging. 15 Interpersonal violence encompasses intimate partner violence (IPV), which can include both TBI and hypoxic-ischemic brain injury from strangulation. In a New York-based study of IPV survivors, refugee status was associated with higher prevalence of IPV and related brain injury, 16 which is consistent with IPV providing additional grounds for survivors seeking asylum protection.…”
Section: Neurological Disorders Across the Migration Journey And Life...mentioning
confidence: 99%
“…14 Gang violence and interpersonal violence is also associated with a higher prevalence of TBI, which is reported in as many as 78% of refugees and asylum seekers, although prevalence estimates are wide-ranging. 15 Interpersonal violence encompasses intimate partner violence (IPV), which can include both TBI and hypoxic-ischemic brain injury from strangulation. In a New York-based study of IPV survivors, refugee status was associated with higher prevalence of IPV and related brain injury, 16 which is consistent with IPV providing additional grounds for survivors seeking asylum protection.…”
Section: Neurological Disorders Across the Migration Journey And Life...mentioning
confidence: 99%
“…Refugees have the human right to health, and countries have obligations to provide refugees and forcibly displaced people health care services. This is delineated in the 1951 Convention Relating to the Status of Refugees and its 1967 Protocol, and is important as prior research has shown a higher prevalence of various neuropsychiatric disorders such as posttraumatic stress disorder (PTSD), depression, and head trauma as well as chronic diseases such as cardiovascular disease . Yet despite both these protections and known health needs, they experience significant health disparities .…”
Section: Introductionmentioning
confidence: 99%
“…This is delineated in the 1951 Convention Relating to the Status of Refugees and its 1967 Protocol, 4 and is important as prior research has shown a higher prevalence of various neuropsychiatric disorders such as posttraumatic stress disorder (PTSD), depression, and head trauma as well as chronic diseases such as cardiovascular disease. 5 , 6 , 7 Yet despite both these protections and known health needs, they experience significant health disparities. 8 They face health care barriers including lack of access and interrupted health care coverage, difficulty navigating complex systems, lack of culturally and linguistically concordant care, discrimination, and poor health care utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, traumatic brain injury (TBI) affects over 60 million individuals [ 14 ] and is the leading cause of disabilities worldwide in comparison with any other injury [ 8 ]. Its high prevalence among forcibly displaced populations is documented alongside the high prevalence of violence suffered and witnessed, but TBI remains under-recognized, partially due to the significant overlap of neurobehavioral post-concussive symptoms and the psychiatric symptoms that are also common in this population [ 15 ]. According to one study that included 139 U.S.-based individuals seeking asylum, nearly half self-reported head injury and were more likely to experience headaches and depression than individuals who did not report head injury [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to one study that included 139 U.S.-based individuals seeking asylum, nearly half self-reported head injury and were more likely to experience headaches and depression than individuals who did not report head injury [ 16 ]. A systematic review found a prevalence of TBI of as high as 78%, although prevalence estimates were wide-ranging due to heterogeneity in the studies [ 15 ]. Fewer studies in the systematic review explored characteristics of head injury in this population, such as common mechanisms of injury, symptoms, and relationships with psychosocial factors.…”
Section: Introductionmentioning
confidence: 99%